Anisotropic surface chemistry properties of salt-type and oxide mineral crystals. (1st August 2020) - Wu, Houqin; Tian, Jia; Xu, Longhua; Wang, Zhoujie; Xu, Yanbo; Gao, Zhiyong; Sun, Wei; Hu, Yuehua
Abstract: Focusing on salt-type and oxide minerals, this paper reviews the research on anisotropic surface chemistry properties, including broken bonds, surface energy, wettability, and surface charge. Moreover, based on the analysis of anisotropic surface properties, the anisotropic adsorption behaviour of reagents on mineral surfaces is also reviewed. The research on anisotropic surface chemistry is instructive to understand some of the properties of the minerals themselves and the reactions in which minerals participate. In addition, the investigation on the anisotropic adsorption behaviour of reagent molecules on mineral surfaces will definitely strengthen the understanding of the efficiency of the interactions. In general, with the knowledge of mineral anisotropy, the relationship between the selective pre-treatment of a mineral and the efficient adsorption of reagent molecules on mineral surfaces will be established.